Identifying Mazama gouazoubira (Artiodactyla; Cervidae) chromosomes involved in rearrangements induced by doxorubicin - Tomazella, Iara Maluf (Genet Mol Biol, 2017)
The process of karyotype evolution in Cervidae from a common ancestor (2n = 70, FN = 70) has been marked by complex chromosomal rearrangements. This ancestral karyotype has been retained by the current species Mazama gouazoubira (Fischer 1814), for which a chromosomal polymorphism (Robertsonian translocations and the presence of B chromosomes) has been described, presumably caused by a chromosome fragility. Thus, this study has identified doxorubicin-induced chromosome aberrations and mapped the regions involved in breaks, which may be related to the chromosome evolution process. G-banding pattern showed that 21 pairs of chromosomes presented chromosomal aberrations, 60% of the total chromosome number of the species M. gouazoubira. Among chromosomes that carry aberrations, the region where they were most frequently concentrated was distal relative to the centromere. These data suggest that certain chromosomal regions may be more susceptible to chromosome fragility and consequently could be involved in karyotype differentiation in species of the family Cervidae.